EFFECTS OF CHEMICAL COMPOSITION AND TEMPERATURE OF HEATING ON THE INFRARED SPECTRA OF LI-SATURATED DIOCTAHEDRAL SMECTITES. (I) MID-INFRARED REGION - Madejova J.; Bujdak J.; Petit S.; Komadel P. (My University, 2000)
Diffuse reflectance spectra in the near-infrared region are presented for Li-saturated smectites heated up to 200°C. The smectites included three montmorillonites, an Fe-beidellite and a ferruginous smectite. Unheated samples showed a complex band near 7060 cm-1 assigned to the first overtone of the OH-stretching mode of structural hydroxyl groups and bound H2O. The OH combination bands appeared in the 4600 4300 cm-1 region. Spectra of heated montmorillonites showed an upward shift and splitting of the OH-overtone band into two components near 7170 and 7110 cm-1. The presence of a band near 7170 cm-1, assigned to the overtone of the AlMgLiOH-stretching vibration, implied that local trioctahedral domains were created upon Li(I) fixation in the previously vacant octahedral positions of montmorillonites. The OH combination bands were shifted to higher frequencies and a new band appeared near 4472 cm-1 in the spectra of montmorillonites heated to temperatures in excess of 130°C. No features indicating Li(I) in the structure of Fe-beidellite or ferruginous smectite were observed in the NIR spectra.